Rumen Degradation Characteristics of Multinutrient Blocks in Semi-Arid Region of Nigeria - Zarah, A I; Mohammed, I D; Abbator, F I (ANIMAL PRODUCTION, 2014)
Abstract.Â  An investigation was carried out on eleven different multinutrient blocks in the semi-arid region of Nigeria. Three crossbred steers fitted with permanent rumen cannula were used to evaluate the nutritional value of multinutrient blocks using the nylon bag techniques. A randomized design was employed to determine the ruminal degradability of multinutrients and their effect on rumen ecology. Approximately 5 g of the feed sample were weighed into duplicated nylon bags (45 Âµ pore size) and incubated ruminally at 0, 6, 12, 24, 48, and 72 h-post feeding.Â  The results showed that the mean values of the ruminal temperature (38.7oC) and pH (6.6) were not different among different incubation. All the multinutrient blocks recorded above 59% DM degradability at 48h period of incubation. The mean values for the potential degradation of the multinutrients were generally high and ranged from 83.2 to 95.8%. It was concluded that inclusion of multinutrients in the diet of ruminants result in a significant improvement in DM degradation in the rumen.Â Key words: digestibility, in vivo technique, multinutrient, ruminantsÂ Abstrak. Penelitian dilakukan terhadap sebelas blok multinutrisi berbeda di wilayah semi-gurun di Nigeria. Tiga sapi peranakan yang diberi pakan dengan âcanulaâÂ  rumen permanen digunakan untuk mengkaji nilai nutrisi dari blok multinutrien menggunakan teknik kantung nilon. Rancangan acak digunakan untuk menentukan kecernaan ruminal multinutrisi dan pengaruhnya pada ekologi rumen. Kurang lebih 5 g sampel pakan ditimbang pada kantong nilonÂ  duplikasi (ukuran pori-pori 45 Âµ) dan diinkubasi ruminal pada 0, 6, 12, 24, 48 dan 72 jam setelah pemberian pakan. Hasil menunjukkan bahwa rataan nilai suhu rumen (38,7oC) dan pH (6.6) tidak berbeda di semua inkubasi. Semua blok multinutrisi tercatat di atas 59% kecernaan BK pada 48 jam inkubasi. Nilai rataan degradasi potensial blok multinutrisi umumnya tinggi dan berkisar antara 83,2 sampai 95,8%. Disimpulkan bahwa penggunaan multinutrisi pada pakan ruminasia menghasilkan peningkatan signifikan pada kecernaan bahan kering di rumen.Â Kata kunci: kecernaan, teknik in vivo, multinutrisi, ruminan